2018
DOI: 10.17523/bia.2018.v75.e1421
|View full text |Cite
|
Sign up to set email alerts
|

Consorciação de estilosantes Campo Grande e capim-marandu em sistemas silvipastoril e sol pleno durante a fase de estabelecimento

Abstract: RESUMO: O objetivo foi avaliar a produção, estrutura e composição botânica dos pastos consorciados de capim-marandu e estilosantes Campo Grande em sol pleno e sistema silvipastoril a diferentes distâncias das árvores durante o estabelecimento. O delineamento foi inteiramente ao acaso com seis repetições, onde avaliaram-se o cultivo em sistema silvipastoril a 2,5 e 5,0 m de distância das árvores e em sol pleno. A massa seca de capim-marandu foi superior no sol pleno (4074,1 kg/ha) em relação ao silvipastoril (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…There was an increase in NTIL as the management height increased. This fact was not observed by Rodrigues et al (2018), in Urochloa brizantha pastures defoliated at 2.5 and 5.0m from trees. The authors did not observe a significant difference in the number of tillers between the different harvesting distances.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…There was an increase in NTIL as the management height increased. This fact was not observed by Rodrigues et al (2018), in Urochloa brizantha pastures defoliated at 2.5 and 5.0m from trees. The authors did not observe a significant difference in the number of tillers between the different harvesting distances.…”
Section: Resultsmentioning
confidence: 74%
“…Thus, the defoliation targets adopted were able to provide satisfactory LSR levels to the animals. On the other hand, Rodrigues et al (2018) observed a significant difference for LSR between SPS and monoculture and between different distances from the tree line. The authors reported that Marandu grass showed higher values for LSR in SPS (1.32) than in full sun (1.13) and a higher LSR at 2.5m from the tree line than at 5.0m, attributing the highest value to the intense shading in that region.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation